Perception of Females Regarding Gender-Based Violence in Jhelum, Pakistan - Maira Gul, Farah Ahmad, Kashaf Aqeel Zaidi, Sara Gull (Pakistan Journal of Medical & Health Sciences, 2023)
Introduction: Gender based violence is not only a violation of women’s basic human rights but also emerged as a major public health issue. This fact is also recognized in Pakistan as a result of international recognition of the problem, its prevalence in the society and documentation of its consequences by various agencies and boom of electronic and social media. Objectives: The main purpose of this dissertation was to assess the causes of gender-based violence and perception of females by interviewing them and to determine the attitude and practices of females regarding gender-based violence in our society. Study Design: This cross sectional study was conducted in District Jhelum between June 2017 to September 2017. Methodology: This was a cross sectional study done in district Jhelum. The calculated sample size was 300 with 1% bound of error and 95% confidence interval. The data was collected through the self-designed questionnaire. Inclusion criteria was women 18 years or above in District Jhelum. Informed consent was taken prior to the interview. Exclusion criteria included women below 18 years of age and those who refused to give consent. Results: 300 female respondents from different regions of District Jhelum were approached. 33.3% of the respondents belonged to the age group of 26-35 years. 29% belonged to the age group of 18-25 years. 21.3% belonged to the 36-45 years of age, 12% belonged to 46-55 years and 4.3% were above 56 years with mean age of 31.5±1.13. 28.3% were single, 65.7% were married, 0.6% were separated, 2% were divorced and 3.3% were widowed. 23.6% of the respondents had primary education, 21.3% had secondary education, 22% had college (diploma/higher diploma) and 33% were undergraduate and post graduate. 41% (n=123) were only house wife while 59% (n=177) were working in private and government institutes. 85.33% (n=256) reported that they have heard about this term, while 14.67% (n=44) reported that they don’t know about gender based violence. While assessing the association between marital status and knowledge it was found that n=163 who were married had knowledge about this term as compared to unmarried (n=77). This showed that married females were more familiar with the gender based violence. Although the study no association of marital status with knowledge (p=0.189> 0.05) using Pearson Chi-Square test. Practical implication Conclusion: The study showed that much of the females are aware of the gender based violence. Depending upon the results of the study it can be concluded that married women suffer more from gender based violence as compared to unmarried women in our society. There are different factors which can lead towards this curse and they should be controlled at the social and community level. The problem should be solved by educating men, by persuasion of community leader, guidance and counseling of men. Keywords: Gender-based violence, Perception, Attitude, Practice, Society.